Refreshed implementation strategy for respectful maternity care through policy dialog in Kenya (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Kenya’s Ministry of Health (MOH) has demonstrated its commitment to quality, respectful health care through the development of national RMNC/PCC policies embedded in existing RMNCAH policies. However, the MOH has identified a gap in the implementation of RMNC policies. Methods: MCGL conducted global and Kenya-specific literature reviews on topics including mistreatment, respectful newborn care, and best practices for RMNC interventions. In addition, qualitative data were obtained through three focused group discussions, and 15 key informant interviews (KIIs) at various levels.Results: Most studies have assessed manifestations, prevalence, and to, to a lesser extent, drivers of disrespect and abuse or mistreatment in facility childbirth. Respondents from the KIIs described cases of mistreatment including harassment, rudeness, denial of services, lack of privacy, and violence. In a 2017 qualitative study, participants described a lack of leadership, stewardship, and accountability toward existing RMNC policies, leading to a lack of implementation. The Kenya Free Maternity Policy recommended that despite this policy, women may still not attend health facilities for maternity care. Newborn experience has largely been excluded from the conversation of RMNC, which has an impact on women and providers with long-lasting effects on their mental health and future care seeking. KIIs were familiar with qualitative methods of measuring mistreatment through exit interviews. Conclusion: Counties are at different stages of advancing respectful care for mothers and newborns and integrating RMNC into existing primary healthcare systems. SA provides evidence regarding the development and implementation of effective RMNC policies and programs both globally and in Kenya.